Integrated transcriptome and metabolome analyses reveals the mechanisms of function loss of Lr29 leaf rust resistance gene at high temperatures in wheat - Wang, Liwen; Yu, Yang; Li, Hang; Lu, Mingzhu; Cao, Shubo; Li, Ziqi; Song, Haoyuan; Purnhauser, Laszlo; Li, Jinlong; Wu, Jiajie (Frontiers in Plant Science, 2025)
Leaf rust (LR) is one of the most common diseases of wheat. The resistance gene Lr29 provides wide resistance to LR, but loses its function under high temperatures. Despite the importance of this gene, the mechanism of resistance is unclear. In this study we investigated the resistance mechanism of the Lr29 gene to LR at the seedling stage, as well as the reasons behind the loss of gene function at high temperatures by using integrated transcriptome and metabolome analyses. Results suggests that the pathways of reactive oxygen species (ROS), which could be due to expression of genes including LOX (lipoxygenase), APX (ascorbate peroxidase) and GST (glutathione S-transferase), play a key role in the resistance of Lr29 to LR, furthermore flavonoids, such as epicatechin, cosmosiin, apiin, vitexin and rutin, were identified as the key metabolites linked to Lr29 resistance. We also found that, at high temperatures, Lr29 downregulated the genes and metabolites associated with glycolysis and the tricarboxylic acid (TCA) cycle, while genes and metabolites related to the shikimic acid pathway were upregulated. This study might provide a valuable theoretical foundation for the cloning of the Lr29 gene, the analysis of its disease resistance mechanism, and the understanding of how temperature affects gene function.